PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN DIVIDEN - Retno Suliati Suleiman; Renita Fetrisia Novita Loka (GoAcademica Research dan Publishing, 2022)
This study aims to analyze profitability, firm size, and managerial ownership of dividend policy. This research uses quantitative research. The data analysis technique used is the classical assumption test which includes normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. For the F test hypothesis see, t test, and the coefficient of determination (R2). The results showed that the variables of profitability, firm size and dividend policy simultaneously had a significant effect on dividend policy. Profitability variable partially has no significant effect on dividend policy, firm size variable has no significant effect on dividend policy while managerial ownership has a significant positive effect on dividend policy.